Cortometraje “La acompañante” - Nina Mamani, Vanessa Sonia (2023)
The following project seeks to show a feminist activist helping women who are planning to get an abortion. This fictional story allows us to learn about the counselors, the way they work and how it affects them emotionally, due to the fact that abortion is considered illegal in Peru. This short film also deals with themes about the relationship between mother and daughter, forced parenthood, and genre roles. These are values forced in peruvian culture.